Social Construction of Gender, Regulatory Bias, and Inequality of Rights in Modern Family Law Systems - Assayuthi, Abdurrahman; Waskito, Sarwo; Evendi, Wakid (Journal of Social Science Studies, 2023)
This study critically examines the social construction of gender roles in family law structures and practices through a thematic qualitative literature review. The synthesis of findings shows that regulatory texts and court practices in the field of family law are heavily influenced by traditional perceptions of male-female relations, as enshrined in the Marriage Law and the Compilation of Islamic Law. The tendency to place men as heads of families and women in the domestic sphere has resulted in systemic barriers to women’s access to essential rights, such as child care, economic rights, and decision-making. The lack of gender-based legal education in formal institutions and the dominance of male actors in the legislative process reinforce the marginalization of women’s rights in the family arena. More progressive legislative efforts still face cultural resistance and implementation barriers in the judicial environment. Although there have been several reform initiatives, real change requires the involvement of cross-sectoral actors—policy makers, advocates, academics, and civil society—to push family law towards greater justice and adaptability to modern social dynamics. This study emphasizes the urgency of strengthening gender equality-based legal education, revising regulations, and increasing women’s representation in family law policy-making as key catalysts for the formation of an inclusive social order and ensuring the equitable distribution of rights within the family.